The Government's Role in Protecting Consumer Rights - Wiwik Sri Widiarty (Universitas Sultan Ageng Tirtayasa, 2022)
The development of banking technology is currently undergoing changes in various fields, especially in internet banking service products. The situation requires everyone to move quickly, not least in the banking sector. This information technology adds value to consumers as service users by allowing them to transact using electronic banking in their daily activities. It is essential to place consumers as users of internet banking services whose rights need to be protected. The government is protecting consumer rights as users of electronic banking services by issuing Consumer Protection Laws and Banking Laws as a legal basis to provide security, convenience, and information rights in online transactions guaranteed by the State. The formulation of the problem in this study is how the government regulates consumer rights for internet banking service products and what the government's role is in providing consumer protection for internet banking service products. This research uses normative juridical research, namely research that focuses on library studies. The part of the government is essential in protecting the community and as a coach for business actors in improving the industrial world and the country's economy.